Early childhood nutrition and health - Azzarri, Carlo (International Food Policy Research Institute, 2014)
More than a decade after becoming a buzzword on the development agenda, governance remains a high priority for the international donor community. This article provides an introduction and overview of key findings from the United Nations University—World Institute for Development Economics Research symposium on “Aiding Government Effectiveness in Developing Countries.” This symposium moves beyond traditional debates about whether aid supports or undermines “good governance” in the aggregate to instead focus on donor interventions in two interrelated governance domains. The first domain examines donor efforts to augment government effectiveness at providing key services to citizens by national and local authorities. Three studies in the collection therefore focus on policing, regulation, and civic education. The second addresses the underlying administrative and financial institutions and processes that facilitate service delivery. Relevant papers in this regard address decentralization, civil service reform, and taxation. In assessing what we know about “what works?” and “what could work?” across these core areas of governance, the contributions shed new light on several key themes, including the dilemma of reconciling governance with ownership, the importance of identifying exactly how context and sequencing matters, and the weaknesses in existing donor evaluation methods. © 2014 The Authors. Public Administration and Development published by John Wiley & Sons, Ltd.